Endurance-based training using various interval sets
It was assumed that EN-1 was normally stimulated by swimming at 80% VO2max. Swimming paces were established at that level and responses compared for different distances, rest periods, and numbers of repeats. It was found that sets of 200 or 400 m repeats produce the best aerobic adaptation as long as the rest interval is no longer than 10 sec. Greater rest intervals introduce an increased anaerobic component. Implications: This type of training is good for establishing aerobic base. It is not likely to influence faster race times but is the stuff of a daily quota of 60 minutes of aerobic work. That volume of work is the amount required to stimulate improvement in aerobic capacity. When training enters the specific preparatory phase, more specific pace work, greater anaerobic adaptation, and energy use proportions appropriate to a targeted race will need to be performed. (ICAR 1990-91 Report)